A gentleman's gentleman - Alexander, T. J. (Vintage Books, a division of Penguin Random House LLC, 2025)
"The notoriously eccentric Lord Christopher Eden is a "man of unusual make" and even more unusual habits: he wears pastels year round, prefers to live as far from the prying eyes and ears of the ton as possible, and wholeheartedly prefers the comfortable company of his childhood cook and aged butler, Plinkton, to any swarm of servants that would normally befit a man of his station. His penchant for privacy makes for a pleasant, if occasionally lonely life-one that threatens to be upended entirely when Christopher receives word from his lawyers that, according to his late father's will, he must find a wife in London by the end of the Season if he intends to maintain his status as the only living heir to the Eden's End estate. While most men his age and status would leap at the chance to marry, he cannot imagine a worse fate. After all, as a "man of unusual make" who also doesn't happen to be attracted to women, his chances of making a wife happy are about on par with his future wife's chances of staying silent about their arrangement. Enter the handsome-if stoic-James Harding, the new valet Christopher very reluctantly hires after Cook and Plinkton remind him that if he's to stay in London, he must keep up appearances befitting that of a wealthy, eligible bachelor. After a rocky start to their relationship (wherein Harding simply does not understand why Christopher won't let him dress him, wait on him, or fulfill any other typical valet duties, for that matter), the two strike up a fragile friendship amid the throes of the London Season-a friendship that threatens to shatter completely as Christopher's deadline to find a wife looms, and Harding reveals that he's been harboring a rather consequential secret of his own. With its heady combination of dry wit, slow-burn romance, and subtle commentary on the complexity of trans identity and relationships that's as relevant now as it was during the Regency era, Eden's End stands to transform the historical romance genre as we know it"--